The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/zaac.201500570
|View full text |Cite
|
Sign up to set email alerts
|

Strontium Chemistry with Silicone Grease

Abstract: Abstract. Reaction of Sr(2-Me 2 N-α-Me 3 Si-benzyl) 2 ·(THF) 2 with one equivalent of DIPP(H)N-BH-N(H)DIPP (NBN-H 2 , DIPP = 2,6-iPr-phenyl) gave the strontium bora-amidinate complex Sr(NBN)·(THF) 4 . Traces of silicone grease, however, can change the course of the reaction completely and gave the product {Sr[(DIPP)NSiMe 2 O]·THF} 4 (1) in a ca. 25 % yield. Complex 1 is a S 4 symmetric cluster with a Sr 4 O 4 core and four chelating amide side arms. From the mother liquor a second product could be isolated: the Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 20 publications
2
41
0
Order By: Relevance
“…At this point of the reaction, the alkaline earth metal ion acts as a convex template, in which the open‐chained ligand species is brought into a suitable conformation for ring closure, which is the final step of the presented reactions. We want to emphasize, that such a mechanism was also postulated by Harder in a past work …”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations
“…At this point of the reaction, the alkaline earth metal ion acts as a convex template, in which the open‐chained ligand species is brought into a suitable conformation for ring closure, which is the final step of the presented reactions. We want to emphasize, that such a mechanism was also postulated by Harder in a past work …”
Section: Resultssupporting
confidence: 54%
“…We want to emphasize, that such am echanism wasalso postulated by Harder in apast work. [31] Further reactions of SrI 2 with the ligands1 ,2-disila [12]crown-4( IV)a nd 1,2-disila-benzo [12]crown-4 (V)w erep erformed. Both ligands are too small for Sr 2+ + and thus, template-assisted ring opening yieldedn ovel species by intermolecular coupling of the respective crown ether.T he reaction of IV with SrI 2 results in the formation of the first disilanyl-bearing [24]crown-8 ether.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the bora‐amidinate complex (NBN)Sr · (THF) 4 {NBN = HB[N(DIPP)] 2 , DIPP = 2,6‐diisopropylphenyl} is active in intramolecular alkene hydroamination (Scheme , top). We also found that reaction of NBN‐H 2 with the dibenzylstrontium reagent Sr(DMAT) 2 · (THF) 2 (DMAT = ortho ‐Me 2 N‐α‐Me 3 Si‐benzyl) in a Schlenk tube with well‐greased joints led to the serendipitous formation of the tetranuclear strontium siloxide/amide cluster 1 ‐Sr that could be isolated in the form of colorless crystals in 24 % yield (Scheme , bottom) . Nucleophilic depolymerization of silicone grease and insertion of the Me 2 SiO‐unit plays a key role in the proposed mechanism .…”
Section: Introductionmentioning
confidence: 92%